PERANAN DAN FUNGSI OMBUDSMAN REPUBLIK INDONESIA DALAM EFEKTIVITAS PENEGAKAN HUKUM - Conie Pania Putri (Program Studi Magister Ilmu Hukum Universitas Kader Bangsa, 2020)
It is hoped that the Ombudsman of the Republic of Indonesia will be able to oversee the delivery of public services and law enforcement for the realization of an effective and efficient, honest, clean, open and free from corruption, collusion and nepotism. The purpose of this study was to determine the obstacles that arise in the role and function of the ombudsman of the republic of Indonesia in the effectiveness of law enforcement and examination and completion of reports by the ombudsman in the effectiveness of law enforcement in Indonesia. The research method in this study is a normative juridical approach where the literature used is to use legislation, as well as books. The conclusion in this study is that in carrying out its duties and functions, the Ombudsman also faces several obstacles, including: a limited number of Human Resources; inadequate facilities and infrastructure, limited budget and resistance from several parties. The efforts made by the Ombudsman in overcoming these obstacles are: improving the performance of the Ombudsman Human Resources effectively and efficiently; take an accountable approach to the Ministry of Finance and Bappenas so that the budget increases so that it can improve facilities and infrastructure and improve the quality of supervision carried out by the Ombudsman.